2013
DOI: 10.3109/14992027.2013.808381
|View full text |Cite
|
Sign up to set email alerts
|

Hearing of 75-year old persons over three decades: Has hearing changed?

Abstract: The hearing, both measured with pure-tone audiometry and with a short questionnaire, of 75-year old persons has not changed at all, or only marginally, over three decades.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 13 publications
0
8
1
Order By: Relevance
“…It has been shown that noise exposure during early occupational life is especially detrimental to the hearing (Muhr et al 2019). Rosenhall et al (2013) compared the same two cohorts included in this study at age 75 and at that age, no significant cohort difference in hearing thresholds and hearing loss prevalence was observed, in either men or women. Although the two compared birth cohorts did not consist entirely of the same participants at 75 years of age as at 85 years of age, the sampling process was the same.…”
Section: Factors Behind the Improvement In Hearing Acuity Among Menmentioning
confidence: 64%
“…It has been shown that noise exposure during early occupational life is especially detrimental to the hearing (Muhr et al 2019). Rosenhall et al (2013) compared the same two cohorts included in this study at age 75 and at that age, no significant cohort difference in hearing thresholds and hearing loss prevalence was observed, in either men or women. Although the two compared birth cohorts did not consist entirely of the same participants at 75 years of age as at 85 years of age, the sampling process was the same.…”
Section: Factors Behind the Improvement In Hearing Acuity Among Menmentioning
confidence: 64%
“…The investigation, which started in 1971, has both longitudinal and cross-sectional designs (9)(10)(11). The ages of the participants of the cohorts range from 70 to 90 years.…”
Section: European Studiesmentioning
confidence: 99%
“…Results derived in the pooled sample were compared to findings reported for the Dutch Rotterdam study [10], the most recent results for the Swedish Gothenburg study [6], the US-American NHANES cycles 1999-2004 [25,4], the cycles 1999 to 2006 [26], and the cycles 2011 to 2012 [5]. Although principally eligible for comparison, the HTL estimates for an earlier Gothenburg cohort were not included in this comparison because the authors stated HTL deviations to earlier cohorts that possibly originated from "differences regarding ambient noise levels in the test rooms used, in combination with difficulties for less experienced testers to detect the problems that arise close to 0 dB HL in a non-insulated test room" [7].…”
Section: Adjustments For Comparison To International Resultsmentioning
confidence: 99%
“…Based on the data sampled in the Gerontological and Geriatric Population Study in Gothenburg, a longitudinal study on the health of 70 year-old people, Hoff et al compared HTL in Swedish 70-year-olds over four decades and found substantial improvements over time [6]. Rosenhall, Möller & Hederstierna, however, referring to data from the same study in Gothenburg, stated that the hearing of 75-year olds had not changed over three decades [7].…”
Section: Introductionmentioning
confidence: 99%